2010
DOI: 10.1080/01416200903332080
|View full text |Cite
|
Sign up to set email alerts
|

A model for teaching midrash in the primary school: forming understandings of rabbinic interpretation of scripture

Abstract: In Jewish primary schools, religious education is centred on the study of Torah. At Sinai, according to Jewish tradition, Moses received the Torah in two parts: a written tradition (Hebrew scripture) and an oral tradition. The oral tradition contained much scriptural interpretation known, in Hebrew, as midrash. Midrash continued to be taught and transmitted by the sages throughout the periods of the two temples. At some later stage, unknown editors, in Roman Palestine, recorded these oral interpretations in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Chumash is the most basic subject of instruction in the early grades in Orthodox schools; it is universally studied across all of these schools, and it is foundational to Orthodox Jewish belief and culture. Previous research (Deitcher 1992;Krakowski 2013;Sigel 2010) has demonstrated that chumash study in Orthodox Jewish day schools almost always integrates midrashic elaboration with textual analysis (particularly in the early years of instruction). Stories drawn from midrashim-homiletical expansions of the biblical text written mainly in late antiquity but whose content is often embedded within later Jewish biblical commentaries from the Middle Ages and after-frame student chumash learning both within the classroom and in other domains, e.g., when listening to sermons in the synagogue.…”
Section: Introductionmentioning
confidence: 99%
“…Chumash is the most basic subject of instruction in the early grades in Orthodox schools; it is universally studied across all of these schools, and it is foundational to Orthodox Jewish belief and culture. Previous research (Deitcher 1992;Krakowski 2013;Sigel 2010) has demonstrated that chumash study in Orthodox Jewish day schools almost always integrates midrashic elaboration with textual analysis (particularly in the early years of instruction). Stories drawn from midrashim-homiletical expansions of the biblical text written mainly in late antiquity but whose content is often embedded within later Jewish biblical commentaries from the Middle Ages and after-frame student chumash learning both within the classroom and in other domains, e.g., when listening to sermons in the synagogue.…”
Section: Introductionmentioning
confidence: 99%